The Metal Abundances across Cosmic Time (MACT) Survey. III – The relationship between stellar mass and star formation rate in extremely low-mass galaxies. Issue 2 (31st October 2020) - Shin, Kaitlyn; Ly, Chun; Malkan, Matthew A; Malhotra, Sangeeta; de los Reyes, Mithi; Rhoads, James E
ABSTRACT: Extragalactic studies have demonstrated that there is a moderately tight (≈0.3 dex) relationship between galaxy stellar mass ( M ⋆ ) and star formation rate (SFR) that holds for star-forming galaxies at M ⋆ ∼ 3 × 10 8 –10 11 M⊙, i.e. the 'star formation main sequence'. However, it has yet to be determined whether such a relationship extends to even lower mass galaxies, particularly at intermediate or higher redshifts. We present new results using observations for 714 narrow-band H α-selected galaxies with stellar masses between 10 6 and 10 10 M⊙ (average of 10 8.2 M⊙ ) at z ≈ 0.07–0.5. These galaxies have sensitive ultraviolet (UV) to near-infrared photometric measurements and optical spectroscopy. The latter allows us to correct our H α SFRs for dust attenuation using Balmer decrements. Our study reveals that: (1) for low-SFR galaxies, our H α SFRs systematically underpredict compared to far-UV measurements, consistent with other studies; (2) at a given stellar mass (≈10 8 M⊙ ), log (specific SFR) evolves as A log (1 + z ) with A = 5.26 ± 0.75, and on average, specific SFR increases with decreasing stellar mass; (3) the SFR– M ⋆ relation holds for galaxies down to ∼10 6 M⊙ (∼1.5 dex below previous studies), and over lookback times of up to 5 Gyr, follows a redshift-dependent relation of log (SFR) ∝ α log ( M ⋆ /M⊙ ) + β z with α = 0.60 ± 0.01 and β = 1.86 ± 0.07; and (4) the observed dispersion in the SFR– M ⋆ relation at low stellar masses is ≈0.3 dex. Accounting for survey selection effects using simulated galaxies, we estimate that the true dispersion is ≈0.5 dex.